PERBEDAAN PENGARUH HIDROGEN PEROKSIDA 35% DAN KARBAMID PEROKSIDA 35% TERHADAP MICROLEAKAGE PADA RESIN KOMPOSIT NANOHYBRID - Istianah Istianah; Endah Aryati Ekoningtyas; Benni Benyamin (ODONTO : Dental Journal, 2015)
Background: Intrinsic tooth discoloration is an aesthetic problem for most people. One of the Intracoronal bleaching treatment used hydrogen peroxide 35% and carbamide peroxide 35%. Tooth whitening material reported increase microleakage in composite resin. Purpose: This research aims to determine the differences effect of hydrogen peroxide 35% and carbamide peroxide 35 % toward microleakage in the nanohybrid composite resin. Method: This research was an experimental laboratory method with post test only control group design. The research was conducted by doing the root canal treatment on 27 samples of maxillary central incisor with the base, then the procedure of intracoronal bleaching was done using hydrogen peroxide 35 % as group 1, carbamide peroxide 35 % as group 2 and distilled water as control group. After nanohybrid composite resin restorative procedure, coated with nail varnish then immersion in methylene blue 5%. Furthermore, slit the teeth and methylene blue penetration depth measured using metalographyÂ  microscope. Result: Based on one way ANOVA test found that there was a difference in each group with a significance of 0,000 (p < 0,05) it can be interpreted that there are differences between groups. Based on LSD Post Hoc test, found that there was a difference in the effect on the group of hydrogen peroxide 35% and carbamide peroxide 35% with a significance of 0,004 (p<0,05). Conclusion: The results of this research can be concluded that there was differences in the effect of hydrogen peroxide 35% and carbamide peroxide 35% towardmicroleakage in the nanohybrid composite resin.Keywords: intracoronal bleaching, hydrogen peroxide 35%, carbamide peroxide 35 %, microleakage, nanohybrid compositeresin